Strength performance and leaching potential of concrete made using wastewater from the UP Lagoon with fly-ash blended cement - Ferma, Anthony Jason T.; San Juan, Jan Nicole Marian M.; Orozco, Christian R. (Quezon City College of Engineering, University of the Philippines Diliman, 2016)
High concrete demand entails the need for a sustainable mix design that involves the efficient use of concrete mix properties. In this study, water and cement are modified to lessen the use of potable water and to reduce CO2 emissions from cement production. The study aims to look into the potential of making concrete using wastewater mixed with Fly-ash Blended cement. Quality of wastewater from the UP Lagoon was tested to determine significant possible effects on the strength of concrete. Samples were made using Fly-ash Blended cement with batches of varying wastewater concentrations (0%, 25%, 50%, 75% and 100%) and water cement ratio (0.5 and 0.5), and tests were done to determine the compressive strength, setting time and leaching potential. Results from HORIBA and photometer analysis showed that wastewater from UP Lagoon passed prescribed standards for mixing water which shows no significant effect on the quality of concrete. Mixing parameters also showed different effects on the strength of concrete. The increase of water to cement ratio caused a decrease in compressive strength, while length of curing age led to improved compressive strength to as much as 194.35% for 0.4 w/c and 34.36% for 0.5 w/c. However, the 90% strength standard of the controlled case required of the samples from 7 days and 28 days of curing was poorly achieved. The setting time of cement is affected by the wastewater concentration used in the mix. Higher concentrations produced longer initial and final setting times that may be attributed to the amount of substances present in the wastewater. The leaching potential of chloride is measured below the standard of 500ppm which implies no corrosion risks due to the use of wastewater. The study concludes that using wastewater with fly-ash blended cement does not produce concrete of acceptable compressive strength.
Thesis (B.S. Civil Engineering)--University of the Philippines Diliman
Keywords: Concrete -- Mixing; Sewage